OSTEOPOROSE EM MULHERES PÓS-MENOPAUSA: GORDURA CORPORAL E SEDENTARISMO - Gelatti, Gabriela T.; Boff, Viviane S.; Kal, Jerry B.; Franz, Ligia B. B.; Bruinsma, Fabiana; Wassermann, Emanuele R. (Salão do Conhecimento, 2013)
Resumo